Fatwa on Sharia Products and Its Role in The Development of Islamic Finance Industry - Faizi Zaini; Mohd Sollehudin Bin Shuib (Islamadina : Jurnal Pemikiran Islam, 2021)
The development of the Islamic finance industry in Indonesia has increased rapidly and satisfactorily. This can be seen from the growing number of Islamic financial institutions with a total of 4,000 institutions in 2019. These thousands of institutions offer sharia services and products; Islamic banks, Islamic people’s credit, sharia insurance, sharia pension funds, sharia pawnshops, sharia cooperatives, and sharia financial technology (fintech), etc. The rapid development of the Islamic financial market is a serious challenge for sharia economic experts who are members of the official institution of the National Sharia Council. This institution has the sole authority in issuing fatwas on sharia economics and finance in Indonesia. This paper reviews the thought products of the National Sharia Council in issuing fatwas in the form of sharia financial products that are flexible, meeting market demands/customer needs, and complying with sharia principles. The data was collected from DSN’s fatwas on sharia products from 1999-2010. Furthermore, the content analysis method was used to analyze the contents of DSN’s fatwa. The analysis result shows that DSN’s ijtihad in producing sharia products has not been sufficient a priori to rely on classical books which are very normative but must rely on economic demands/needs of modern financial markets.